(untitled) (Revista Ciência Agronômica, 2020)
The aim of this work was to study the effects of green manure, Trichoderma asperellum and homeopathy on the agronomic performance of the biquinho pepper (Capsicum chinense Jacq.). The design was of randomised blocks with four replications, in subdivided plots, with homeopathic remedies applied in the plots: 1) Arnica montana 6CH; 2) Pulsatilla nigricans 6CH; and 3) no homeopathic remedies; and seven treatments applied in the sub-plots: 1, 2 and 3) Crotalaria juncea ‘IAC-KR-1’ (sunn hemp P50 D25, P50 D50, and P0 D50); 4) Canavalia ensiformis (common jack-bean P0 D25); 5) Cajanus cajan ‘IAPAR 43 Aratã’ (pigeon-pea 00 D25); 6) Trichoderma asperellum; and 7) control (with no green manure or T. asperellum). The green manure was sown at a density of 25 kg ha-1 (D25) and 50 kg ha-1 (D50) when transplanting the biquinho pepper (P0) and 50 days prior to transplanting (P50). The stem height and diameter, relative chlorophyll index, normalised difference vegetation index (NDVI), and fruit production were evaluated in the biquinho pepper. The intercrop with sunn hemp, sown 50 days before transplanting at a density of 50 kg ha-1, increased the height of the pepper plant by 8%, added 0.47 kg ha-1 dry biomass to the system, and showed similar productivity to the control treatment. The pepper plants treated with Pulsatilla nigricans 6CH were taller and had a larger stem diameter, with an increase of 11% and 6% respectively. Homeopathy had no influence on productivity in the pepper. T. asperellum brought no benefits to the biquinho pepper.